Boattr: digital arts and low impact life on the towpath. Issue 2 (4th May 2019) - Hadzi, Adnan
ABSTRACT: This article discusses the towpath/'network' of the British Waterways as a digital social commons, through the researcher's journey on the narrow boat Quintessence and the development of the boattr prototype in collaboration with fellow boaters (bargees), the MAZI (for 'together' in Greek) project, a Horizon2020 research project, and the 7067 – It's not a Test radio performance. For three years the researcher (Dr Adnan Hadzi) together with his partner, the documentary photographer Natascha Sturny, joined the community of bargees. The article uses as a basis the boat logs created over the MAZIzone, in a diary format, to address the urban commons topic in a broader more poetic approach analysing three projects, namely the boattr prototype, MAZIzone, and 7067 – It's not a Test, divided into the three years, of which each is dedicated to one of the projects. Alongside the edited diary texts, a selection of images taken during those three years illustrates this article. In the boattr 360 installation audiences can interact with the MAZIzone viewing image galleries and 360 videos of the boat journey.